Hyperglycemia and diabetes have different impacts on outcome of ischemic and hemorrhagic stroke - Snarska, Katarzyna K. (Arch Med Sci, 2016)
INTRODUCTION: Stroke is the second leading cause of long-term disability and death worldwide. Diabetes and hyperglycemia may impact the outcome of stroke. We examined the impact of hyperglycemia and diabetes on in-hospital death among ischemic and hemorrhagic stroke patients. MATERIAL AND METHODS: Data from 766 consecutive patients with ischemic (83.15%) and hemorrhagic stroke were analyzed. Patients were classified into four groups: ischemic and diabetic; ischemic and non-diabetic; hemorrhagic and diabetic; and hemorrhagic and non-diabetic. Serum glucose was measured on admission at the emergency department together with biochemical and clinical parameters. RESULTS: Mean admission glucose in ischemic stroke patients with diabetes was higher than in non-diabetic ones (p < 0.001) and in hemorrhagic stroke patients with diabetes than in those without diabetes (p < 0.05). Mean admission glucose in all patients who died was significantly higher than in patients who survived. In multivariate analysis, the risk factors for outcome in patients with ischemic stroke and without diabetes were age, admission glucose level and estimated glomerular filtration rate (eGFR), while in diabetics they were female gender, admission glucose level, and eGFR; in patients with hemorrhagic stroke and without diabetes they were age and admission glucose levels. The cut-off value in predicting death in patients with ischemic stroke and without diabetes was above 113.5 mg/dl, while in diabetics it was above 210.5 mg/dl. CONCLUSIONS: Hyperglycemia on admission is associated with worsened clinical outcome and increased risk of in-hospital death in ischemic and hemorrhagic stroke patients. Diabetes increased the risk of in-hospital death in hemorrhagic stroke patients, but not in ischemic ones.